SEVERAL ISSUES OF TEACHING GYMNASTICS IN MIDDLE SCHOOLS - Rumiya Salikhova; Valentina Shank (American Journals Publishing, 2024)
What should be paid attention to in the more effective organization of gymnastics classes in general secondary schools of our republic, what methods should be used when conducting classes, and medical groups in physical education? The state of students' sports preparation and stages.
Keywords: Forms of physical exercises, physical education class, general tasks, special tasks, medical groups, tasks of physical education, volitional qualities, tool, gymnastics term, skill, skill, volitional qualities.